Carbon-based functional nanomaterials: Preparation, properties and applications - Li, Zihao; Wang, Ling; Li, Yu; Feng, Yiyu; Feng, Wei (Composites science and technology, 2019)
Carbon-based functional nanomaterials have attracted remarkable attention from the scientific community for their unique combinations of advantageous chemical and physical properties, such as superb electrical conductivity, excellent heat conductivity, chemical stability, advanced optical properties, and high mechanical strength. Our research group has been very actively involved in the study and further development of carbon-based functional nanomaterials and their potential applications for many years. In this feature article, we introduce our recent endeavors in the development of carbon-based nanomaterials with superior functionalities for potential application in diverse fields including solar thermal fuels, advanced thermal management, and electrochemical energy storage. The key design concepts of these advanced functional nanomaterials are highlighted, specific synthesis strategies are discussed, their potential usage in devices and applications is emphasized, and background information is succinctly furnished wherever warranted. We begin with an overview on the chemistry of carbon nanomaterials, in which the synthesis and chemical functionalization of carbon nanotubes and graphene are introduced, respectively. We then showcase the design, fabrication and properties of different functional carbon nanomaterials for diverse applications, including photoactive azobenzene/carbon nanomaterials for solar thermal fuels and light-driven carbon-based actuators, advanced carbon nanomaterials with directional thermal conductivity, and carbon-based electrodes for electrochemical energy storage. Finally, we conclude by briefly summarizing the advantages of the application of functional carbon-based nanomaterials in various fields, and list challenges that remain to be solved and potential that remains to be tapped.